Molecular docking and dynamic simulation of 3-dehydroquinate dehydratase from Mycobacterium Tuberculosis - MUSTAFA ALHAJI ISA; BALWANT KISHAN MALIK (International Journal of Pharma and Bio Sciences, 2017)
Tuberculosis is the most common cause of death due to an infectious agent known as Mycobacterium tuberculosis. Therefore, the aim of this study was to identify novel inhibitors of 3-dehydroquinate dehydratase of Shikimate pathway using both natural and synthetics ligands libraries. Three dimensional structure (3D) of 3-dehydroquinate dehydratase was retrieved from Protein Data Bank (PDB ID: 3N76) and subjected to energy minimization and protein optimization. Virtual screening was performed based on physicochemical properties (Lipinski rule of five) and biological activity. Molecular docking analysis of protein-ligand complex was carried out using AutoDock4.0 for both synthetic and natural ligands (PubChem Database and Zinc Database). Molecular Dynamic (MD) simulation was also performed to determine the stability of protein-ligand complex using CHARMM (Chemistry at Harvard Macromolecular Mechanics) force field in NAMD v2.12 (Nanoscale Molecular Dynamic Program). The results of molecular docking revealed that five molecules had high binding energy (ZINC14981770, ZINC01147665, ZINC22910025, ZINC8442077 and PubChem72341) range between -8.99 and -8.39 kcal/Mol. Leu14, Gly15, Gly18, Glu21, Tyr25, Gln52, Asp54, Gln58, Asp76, Gly79, Ile103 and Arg109 stabilised the protein-ligand complex through theformation of hydrogen bonding.Lastly, the ligands were further screening for pharmacokinetic properties based on Absorption, distribution, metabolism, excretion and toxicity (ADMET) properties. Therefore, these ligands will be recommended for the treatment of tuberculosis after successful in vitro and in vivo biological assay.